Peningkatan Perkembangan Motorik Halus Anak Usia Dini Melalui Kegiatan Finger Painting di SPS Tsamrotul Jannah - Rohmah, Wasilatul (INNOVASI : JURNAL INOVASI PENDIDIKAN, 2025)
This study aims to improve the fine motor development of early childhood through finger painting activities at SPS “Tsamrotul Jannah.” The method used is Classroom Action Research (CAR) conducted in two cycles, each consisting of the stages of planning, implementation, observation, and reflection. The research subjects consisted of 15 children aged 4–5 years Data were collected through observation sheets, visual documentation, and field notes, then analyzed descriptively using quantitative and qualitative approaches. The results showed a significant improvement in children’s fine motor skills, such as grasping, pinching, arranging small objects, drawing patterns, and controlling finger pressure. The average indicator achievement increased from 50% in the first cycle to 80% in the second cycle. The finger painting activity proved effective in stimulating fine motor skills while creating a fun and engaging learning environment. Therefore, finger painting can be used as a creative and practical learning method in early childhood development.